2015
DOI: 10.1017/s0033291715002457
|View full text |Cite
|
Sign up to set email alerts
|

A prospective longitudinal model predicting early adult alcohol problems: evidence for a robust externalizing pathway

Abstract: Background Risk factors for alcohol problems (AP) include biological and environmental factors that are relevant across development. The pathways through which these factors are related, and how they lead to AP, are optimally considered in the context of a comprehensive developmental model. Method Using data from a prospectively assessed, population-based UK cohort, we constructed a structural equation model that integrated risk factors reflecting individual, family and peer/community-level constructs across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
55
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 66 publications
(81 reference statements)
13
55
1
2
Order By: Relevance
“…Traits with only moderate heritability (such as alcohol dependence) potentially may require even larger samples relative to model traits (e.g., height) to achieve comparable gains in terms of variance explained. From a developmental perspective, the small magnitude of effect of PRS and AUP may also reflect a lesser role of genetic factors for alcohol-related phenotypes during the earlier stages of development compared with the later stages Kendler et al, 2008;Rose et al, 2001), highlighting the salience of environmental factors such as easier access to alcohol and enhanced social pressures that allow genetic liabilities to develop (Edwards et al, 2016). An important note is that we created our PRS using GWAS estimates from FinnTwin12 because of the similarity of the sample to ALSPAC, with it also being a population-based study of alcohol use outcomes in young adulthood; however, it is plausible that with an older adult sample, PRS may have also had a larger magnitude of effect on AUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traits with only moderate heritability (such as alcohol dependence) potentially may require even larger samples relative to model traits (e.g., height) to achieve comparable gains in terms of variance explained. From a developmental perspective, the small magnitude of effect of PRS and AUP may also reflect a lesser role of genetic factors for alcohol-related phenotypes during the earlier stages of development compared with the later stages Kendler et al, 2008;Rose et al, 2001), highlighting the salience of environmental factors such as easier access to alcohol and enhanced social pressures that allow genetic liabilities to develop (Edwards et al, 2016). An important note is that we created our PRS using GWAS estimates from FinnTwin12 because of the similarity of the sample to ALSPAC, with it also being a population-based study of alcohol use outcomes in young adulthood; however, it is plausible that with an older adult sample, PRS may have also had a larger magnitude of effect on AUP.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, molecular genetic studies have found that sensation seeking mediated the association between a variable number of tandem repeat polymorphism in the DRD4 gene and alcohol-related outcomes in adolescents and collegeaged adults (Laucht et al, 2007;Ray et al, 2009). Sensation seeking assessed during adolescence was also a significant contributor to a developmental model (along with early conduct problems and adolescent AUP) that explained more than 30% of the variance in liability for AUP by early adulthood (Edwards et al, 2016). Taken together with the current findings, high sensation seeking during childhood or early adolescence may be an important constituent in the risk pathway underlying later AUP.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol use and problems are quite common: over 50% of US adults report drinking within the past month (SAMHSA, 2014); 6.7% report heavy drinking in the past month (SAMHSA, 2014); and nearly 30% of adults meet criteria for a lifetime DSM-5 diagnosis of Alcohol Use Disorder (AUD) (Grant et al, 2015). Pathways leading to AUD are complex and diverse, consisting of familial factors (both biological and otherwise), environmental influences, and psychological and other individual-level factors (Kendler et al, 2011, Edwards et al, 2016, Jessor, 1991). Furthermore, the effects of these factors may differ between alcohol use outcomes, including initiation, typical consumption, problems, and alcohol addiction resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, among environmental influences, parental involvement and peer substance use/peer deviance have emerged as consistent predictors of alcohol use and misuse during adolescence (Sher et al, 2005). Additionally, a family history of alcohol problems is predictive of alcohol problems during young adulthood (Kendler et al, 2011, Edwards et al, 2016), though this combines both genetic and environmental risk.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an increased risk for adult psychopathology in individuals with mental health problems in childhood (Caspi et al, 1996;Reef et al, 2009). Externalizing problems in childhood also have been found to predict other problems such as adult alcohol problems (Edwards et al, 2015), and adult criminality (Satterfield et al, 2007). Early detection and intervention is thus crucial to prevent negative development.…”
Section: Course and Comorbiditymentioning
confidence: 99%